An observational study of maternal and fetal outcome in pregnant women with Hepatitis E - Mishra, Ranjana; Nayak, Arun H.; Mehendale, Madhuri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hepatitis E in pregnancy has been a subject of interest in the recent years as the available research work is very limited and conflicting especially in pregnant women as compared to infection in men and non- pregnant women in which the disease is usually self- limiting. The mechanism of liver injury in hepatitis E is not clear and no conclusive theories about the exact pathogenesis are available. This study was done to gain insight into the effects of hepatitis E virus on pregnancy in terms of maternal and fetal outcome. Methods: Total of 40 pregnant women with Hepatitis E Virus IgM antibodies was included in the study. Hepatitis cases due to other viral and non-infective causes were excluded. Maternal outcomes in terms of mode of delivery, complications like PPH, hepatic encephalopathy, fulminant hepatic failure, coagulopathy and maternal mortality was studied. Fetal outcomes in terms of intrauterine fetal deaths, stillbirth, live births, and neonatal deaths were studied. Results: This study showed high mortality rates (42.5%) in pregnant women with hepatitis E. The most common obstetric complication was IUFD (45%) followed by preterm labor (32.5%) and postpartum hemorrhage (22.5%). Hepatic encephalopathy (62.5%) was the commonest medical complication followed by coagulopathy (25%). A statistically significant association was found between the presence of medical complications and poor maternal outcome. Conclusions: Hepatitis E virus infection in pregnancy often has a fulminant course with poor maternal and fetal outcome. Its management therefore requires an early diagnosis, and a multidisciplinary approach.